Effects of single injection of naloxone and damgo within nucleus accumbens septi in the plus maze test in rats - Morsucci, Cristian (2018)
Nucleus accumbens septi (NAS) is studied because its relations with cognition and anxiety. Its pharmacological manipulation is widely used in experimental psychopathology to reproduce psychotic signs and symptoms in animal models. In the present study, the effect of the injection of an agonist and a µ-receptor antagonist in this structure is assessed. Holtzman strain male rats (240-290 g) were cannulated bilaterally in NAS. One week after the injection they were subjected to an anxiety test, prior saline injection (controls), DAMGO ([D-Ala2, N-MePhe4, Gly-ol]-encephalin, opioid agonist) or naloxone (opioid antagonist). We evaluated the set of parameters classically considered in our laboratory (open arm time, time per entry, open arm entries, closed arm entries, open/closed arm quotient, open and closed arm ends arrivals, rearing, fecal bowls and grooming behaviors. There was only a significant increase in the length of stay in the open arm with the injection of DAMGO (0.2 µg/1 µL, p < 0.05) and a significant increase in grooming behaviors with naloxone (1 µg/1 µL, p < 0.001), compared with saline controls (1 µL). We conclude that the receptor stimulation in NAS generates effects compatible with anxiolysis, and blocking of such receptor in said structure results in an increase in grooming behaviors.